BUSINESS STRATEGY AND INNOVATIVE PRACTICES ON SERVICES INDUSTRY IN INDONESIA SETTING - Achmad Hidayat Sutawidjaya (Business and Entrepreneurial Review, 2010)
This study explores how firms on services industry (cellular company) in indonesia setting with different strategic orientations manage innovative practices. Specifically, we examine differences in how firms with contrasting strategic orientations view the environmental and organizational factors that influence their management of innovation. This study contributes to the integration of the strategic management and innovation perspective by empirical examining how innovative practices vary among firms on services industry in indonesia setting with different strategic orientation, thereby achieving tighter integration between these two important theoretical perspective. In doing this research, we begin to address some important questions which are likely to be crucial interest to both scholars and practicing managers. This study proceeds as follows, we first established a foundation for our study by examining the literatures on strategy and innovation. We then develop hypotheses on relationship between a firm’s strategy type and its management of innovation (innovative practice, product innovation), external advantage, internal advantage. We the test hypotheses using data from 3 firms of cellular company (XL, Satelindo, Telkomsel) with sample 87 Manager randomly. A discussion of the empirical results and conclusion there is strong relationship between a firm’s strategy type and its management of innovation on services industry (cellular company) in indonesia setting